Digital Literacy Development in Madrasah Aliyah: Evidence From a Web-Based Learning Intervention - Fitriah Artina; Karim Suryadi; Iim Siti Masyitoh; Syaifullah Syaifullah; Muhammad Amin (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2026)
In the global digital era, digital literacy has emerged as a critical educational concern, extending beyond merely technical competence to encompass ethical awareness, social integration, and responsible participation in increasingly polarized digital environments. This study, therefore, examines the effectiveness of the MPIS application in enhancing digital literacy among students in Madrasah Aliyah. A quasi-experimental design with a pre-test and post-test control group was employed, involving 64 Madrasah Aliyah students selected through cluster random sampling from a population of 150 students across twelve classes. Data were collected using a validated digital literacy assessment consisting of 20 multiple-choice items, which were then analyzed using normalized gain (N-gain) analysis and independent samples t-tests. The results show that students who used the MPIS application demonstrated higher post-test digital literacy scores; specifically, their mean scores increased from 35 to 85, with an N-gain of 0.75. In contrast, the control group receiving conventional instruction showed an N-gain of 0.45. These findings, therefore, indicate that web-based learning interventions can effectively support the development of students’ digital literacy in Madrasah contexts. Moreover, the study suggests that integrating digital learning tools into Islamic education has the potential to support character-oriented learning, encourage ethical and responsible technology use, and ultimately contribute to more inclusive and constructive digital engagement.